2010
DOI: 10.1007/s12402-010-0046-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and effectiveness of a structured disorder tailored psychotherapy in ADHD in adults: study protocol of a randomized controlled multicentre trial

Abstract: ADHD is a serious risk factor for co-occurring psychiatric disorders and negative psychosocial consequences in adulthood. Previous trials on psychotherapeutic concepts for adult ADHD are based on behavioural (cognitive behavioural and dialectical behavioural) psychotherapeutic approaches and showed significant effects. The aim of our study group (COMPAS) is to carry out a first randomized and controlled multicentre study to evaluate the effects of a disorder tailored psychotherapy in adult ADHD compared to cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 36 publications
1
54
0
2
Order By: Relevance
“…In an attempt to explore the potential of the abovementioned dysconnectivity as a biological marker for BPD, it is recommended that future studies should also carry out functional connectivity analyses in the most commonly documented comorbidities of BPD, which are MDD, attention deficit hyperactivity disorder (ADHD), and PTSD. PTSD is of particular interest given that both BPD and PTSD are highly related to experiences of trauma (Zetzsche et al, 2006;Pagura et al, 2010;Philipsen et al, 2010;Stein et al, 2010), and many common neurobiological abnormalities have been identified between the two (O'Neill et al, 2013). Although MDD was the only comorbidity that was allowed in our BPD sample, which increased the homogeneity of the sample, this in itself may limit the generalisability of the findings given the high occurrence of other/additional comorbidities found in the wider population of individuals with BPD.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to explore the potential of the abovementioned dysconnectivity as a biological marker for BPD, it is recommended that future studies should also carry out functional connectivity analyses in the most commonly documented comorbidities of BPD, which are MDD, attention deficit hyperactivity disorder (ADHD), and PTSD. PTSD is of particular interest given that both BPD and PTSD are highly related to experiences of trauma (Zetzsche et al, 2006;Pagura et al, 2010;Philipsen et al, 2010;Stein et al, 2010), and many common neurobiological abnormalities have been identified between the two (O'Neill et al, 2013). Although MDD was the only comorbidity that was allowed in our BPD sample, which increased the homogeneity of the sample, this in itself may limit the generalisability of the findings given the high occurrence of other/additional comorbidities found in the wider population of individuals with BPD.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol and diagnostic procedure were implemented within the clinical COMPAS trial. 29,30 Appendix 1, Table S1, available at jpn.ca, lists the eligibility criteria for study partici pation. Appendix 1, Table S2 lists the applied diagnostic instruments.…”
Section: Patient Recruitment and Assessmentmentioning
confidence: 99%
“…Group psychotherapy or CM plus a medication number (coding for MPH or placebo) were centrally assigned to each patient. 29,30 Treatments were allocated with a 1:1:1:1 ratio, stratified by centre. 31 Patients and therapists were blinded for medication, but were aware of the assignment to either GPT or CM.…”
Section: Randomization and Maskingmentioning
confidence: 99%
See 2 more Smart Citations